Jesting culture and religious politics in seventeenth-century England. Issue 267 (16th December 2021) - Somers, Tim
Abstract: This article argues that jestbooks performed important functions within seventeenth-century religious politics. These functions were distinct from the 'biting' polemic and satire that more often catches the eyes of scholars. The article identifies ubiquitous 'popular jests' and discusses how jesting opened up space to engage playfully with controversial topics. In doing so, it challenges the historiographical dominance of the 'superiority theory' of laughter and the othering of dissenters and Catholics. The second section discusses jesting in relation to tension in the 1630s, while the final section discusses royalism, humorous manuscript chronicling and the way jesting shaped the memory of the civil wars.